Assessing the Convergence of International Agricultural Markets as a Prerequisite for Rapeseed Sale at New Markets - Tanasiichuk, Alona; Hromova, Olha; Abdullaieva, Anastasiia; Kovtun, Eduard; Marshuk, Lina (European Journal of Sustainable Development, 2021)
The article is devoted to the study of the state of the market of agro-industrial products, which is an integral part of the world market and one of the most important parts of the economic systems of most countries with market economies. It has been determined peculiarities of modern development of domestic export-oriented industries, among which are raw materials, dependence on market fluctuations on world markets. The analysis of oilseeds production volumes has been done, in particular rapeseed; the dynamics of export-import volume operations with the product group «1205 Seeds of cole or rapeseed, whether ground or not ground» has been also done. A system of indicators has been developed to assess the convergence of international agricultural markets as a prerequisite for the sale of rapeseed to new international markets. The markets of the Czech Republic and the United Arab Emirates have been identified as particularly promising markets for the sale of Ukrainian agricultural products of the commodity group «1205 Seeds of cole or rapeseed, whether ground or not ground». Assessment of the convergence indicators of the new international markets of the Czech Republic and the United Arab Emirates allowed us to conclude that these markets demonstrate convergent conditions for doing business in them by Ukrainian farmers. The most important tasks facing Ukrainian agricultural producers are substantiated: prevention of reduction of sown areas of oilseeds, production volumes of commodity group increase «12 Seeds and fruits of oilseeds», introduction to new international markets of commodity group «1205 of Ukrainian production».